Clinically insignificant prostate cancer suitable for active surveillance according to Prostate Cancer Research International: Active surveillance criteria: Utility of PI‐RADS v2. Issue 4 (13th September 2017) - Yim, Jae Hyun; Kim, Chan Kyo; Kim, Jae‐Hun
Abstract : Background: Active surveillance (AS) is an important treatment strategy for prostate cancer (PCa). Prostate Imaging‐Reporting and Data System (PI‐RADS) v2 has been addressed, but few studies have reported the value of PI‐RADS v2 for assessing risk stratification in patients with PCa, especially on selecting potential candidates for AS. Purpose: To investigate the utility of PI‐RADS v2 and apparent diffusion coefficient (ADC) in evaluating patients with insignificant PCa, who are suitable for AS. Study Type: Retrospective. Subjects: In all, 238 patients with PCa who met the Prostate Cancer Research International: Active Surveillance criteria underwent radical prostatectomy. Field Strength/Sequence: 3.0T, including T2 ‐weighted, diffusion‐weighted, and dynamic contrast‐enhanced imaging. Assessment: Insignificant cancer was defined histopathologically as an organ‐confined disease with a tumor volume <0.5 cm 3 without Gleason score 4–5. Patients were divided into two groups based on the PI‐RADS v2 and tumor ADC: A, PI‐RADS score ≤3 and ADC ≥1.095 × 10 −3 mm 2 /s; and B, PI‐RADS score 4–5 or ADC <1.095 × 10 −3 mm 2 /s. Preoperative clinical and imaging variables were evaluated regarding the associations with insignificant cancer. Results: Of the 238 patients, 101 (42.8%) were diagnosed with insignificant cancer on pathological findings. The number of positive cores, prostate‐specific antigen density (PSAD), PI‐RADS v2 and tumor ADC were significantly associated with insignificant cancer on univariate analysis ( P < 0.05). However, multivariate analysis indicated tumor ADC (odds ratio [OR] = 4.57, P < 0.001) and PI‐RADS v2 (OR = 3.60, P < 0.001) were independent predictors of insignificant cancer. Area under the receiver operating characteristics curve (AUC) reached 0.803 when PI‐RADS v2 (AUC = 0.747) was combined with tumor ADC (AUC = 0.786). Data Conclusion: The PI‐RADS v2 together with tumor ADC may be a useful marker for predicting patients with insignificant PCa when considering AS. Level of Evidence: 4 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1072–1079.